Rare B decays at e+e− colliders - Tiwary Rahul (EPJ Web of Conferences)
The rare decays of B mesons offer a prime opportunity to test predictions of the Standard Model and to search for effects beyond the Standard Model. The coherent production of B mesons at e+e− colliders provides a clean experimental setup for these studies. In this paper, we discuss the recent results of rare B decays from the Belle and Belle II experiments.